Effectiveness of psychosocial interventions for infertile women: a systematic review and meta-analysis with a focus on a method-critical evaluation - Kremer, Franziska; Ditzen, Beate; Wischmann, Tewes (PLOS ONE, 2023)
Background Approximately seven to nine percent of couples of reproductive age do not get pregnant despite regular and unprotected sexual intercourse. Various psychosocial interventions for women and men with fertility disorders are repeatedly found in the literature. The effects of these interventions on outcomes such as anxiety and depression, as well as on the probability of pregnancy, do not currently allow for reliable generalisable statements. This review includes studies published since 2015 performing a method-critical evaluation of the studies. Furthermore, we suggest how interventions could be implemented in the future to improve anxiety, depression, and pregnancy rates. Method The project was registered with Prospero (CRD42021242683 13 April 2021). The literature search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Six databases were searched and 479 potential studies were discovered. After reviewing the full texts, ten studies were included for the synthesis. Not all studies reported the three outcomes: four studies each for depression, three for anxiety and nine studies for pregnancy rates were included in the meta-analysis, which was conducted using the Comprehensive meta-analysis (CMA) software. Results Psychosocial interventions do not significantly change women’s anxiety (Hedges’ g -0,006; CI: -0,667 to 0,655; p = 0,985), but they have a significant impact on depression in infertile women (Hedges’ g -0,893; CI: -1,644 to -0,145; p = 0,026). Implementations of psychosocial interventions during assisted reproductive technology (ART) treatment do not increase pregnancy rates (odds ratio 1,337; 95% CI 0,983 to 1,820; p = 0,064). The methodological critical evaluation indicates heterogeneous study design and samples. The results of the studies were determined with different methods and make comparability difficult. All these factors do not allow for a uniform conclusion. Methodological critical evaluation Study design (duration and timing of intervention, type of intervention, type of data collection) and samples (age of women, reason for infertility, duration of infertility) are very heterogeneous. The results of the studies were determined with different methods and make comparability difficult. All these factors do not allow for a uniform conclusion. Conclusion In order to be able to better compare psychosocial interventions and their influence on ART treatment and thus also to achieve valid results, a standardised procedure to the mentioned factors is necessary.